Analisis peran tanaman toga daun sirih hijau (piper betle l.) Sebagai terapi alami radang tenggorokan - Mundari, Bintang Maulana (Maliki Interdisciplinary Journal, 2026)
Sore throat is a common health problem and can reduce the quality of life of sufferers. The use of chemical drugs has the potential to cause side effects, so safer alternative treatments are needed, one of which is through the use of family medicinal plants (TOGA). This study aims to analyze the role of green betel leaves (Piper betle L.) as a natural therapy in treating sore throats. The method used is library research by reviewing various literature sources such as national and international scientific journals, books, official reports, and trusted websites. The results of the study indicate that green betel leaves contain active compounds such as betephenol, flavonoids, tannins, saponins, alkaloids, and phenols that have antibacterial, anti-inflammatory, antioxidant, and analgesic activities. Various previous studies have proven the effectiveness of green betel leaf extract in inhibiting the growth of bacteria that cause sore throats, reducing inflammation, and relieving pain. Thus, green betel leaves have the potential to be used as a natural supportive therapy in treating sore throats, although further clinical research is needed to confirm their effectiveness and safety.